2017
DOI: 10.3897/neobiota.36.11418
|View full text |Cite
|
Sign up to set email alerts
|

Plant parasitic nematode survival and detection to inform biosecurity risk assessment

Abstract: Plant parasitic nematodes (PPN) are known to survive periods of desiccation, an ability that increases the risk of them surviving unintentional transport between countries. To investigate nematode survival in soil subject to prolonged storage, soil collected from a native forest and an organic orchard was stored separately in cupboards at ambient temperature for 36 months. Subsamples were taken at 0, 3, 6, 12, 13, 24 and 36 months to determine the presence of plant parasitic and total nematodes using a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Pratylenchus is observed in >90% of pasture soil samples throughout New Zealand (Yeates 1981;Skipp & Christensen 1983;Knight 2001;McNeill et al 2015) and large populations have been associated with a lack of plant response to applied fertilisers (Yeates 1976). Some Pratylenchus species are able to withstand long periods of desiccation (Das Neves et al 2012;Aalders et al 2017), which probably assists their ability to persist in most soil situations. Heterodera populations occur throughout the country and in both lowland and hill country situations (Skipp and Christensen 1983;Mercer and Woodfield 1986).…”
Section: Life Cycle and Biologymentioning
confidence: 99%
“…Pratylenchus is observed in >90% of pasture soil samples throughout New Zealand (Yeates 1981;Skipp & Christensen 1983;Knight 2001;McNeill et al 2015) and large populations have been associated with a lack of plant response to applied fertilisers (Yeates 1976). Some Pratylenchus species are able to withstand long periods of desiccation (Das Neves et al 2012;Aalders et al 2017), which probably assists their ability to persist in most soil situations. Heterodera populations occur throughout the country and in both lowland and hill country situations (Skipp and Christensen 1983;Mercer and Woodfield 1986).…”
Section: Life Cycle and Biologymentioning
confidence: 99%
“…In addition to local spread in irrigation water, dispersal of H. zeae is aided by its survival for long periods in the absence of hosts. Viability for 3-7 years under transit conditions has been observed (Aalders, McNeill, Bell, & Cameron, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nematodes were rapidly killed in freezing temperatures [ 27 ] and above 20 °C [ 30 ]. Interestingly, Pratylenchus species, one of the common PPNs, were found to be infective even after 36 months of storage at 12.5 °C [ 26 ]. Whether nematodes are dead or alive in stored soil, the molecular analysis of nematodes in soil should not be affected substantially by the physical conditions of the nematodes since DNA from both dead and live nematodes would be accounted for in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the storage time may not directly influence the molecular analysis of soil, but other environmental factors may, such as soil pH, soil type, vegetation, and soil handling before storage [ 45 ]. In all studies with PPNs, nematode numbers gradually decreased over time even at the optimal storage temperature [ 26 , 27 , 28 , 31 ]. In a proteomic study with entomogenic nematodes at two storage temperatures (9 °C and 20 °C), it was found that the proteome of the nematodes was affected by temperature, as well as nematode species [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation